Visceral Leishmaniasis in HIV-Infected Patients: The Challenge of Relapse and Treatment Failure - Cipriano, Patrícia (2017)
Introduction: Visceral leishmaniasis is an endemic disseminated infection, considered to be the third most frequent opportunistic parasitic infection in Europe. It is especially prevalent in patients co-infected with human immunodeficiency virus, in whom it poses a great therapeutic challenge due to increased risk of relapse. The goal of this study is to characterize a population of co-infected patients, as well as the efficiency of the adopted treatment strategies.Material and Methods: Retrospective study with a sample composed of all patients with visceral leishmaniasis and human immunodeficiency virus admitted in an Infectious Diseases ward over a period of 10 years.Results: Of the 23 enrolled patients, two were female (8.7%). The mean TCD4+ cell count was 104.4 cells/uL (± 120.3cells/uL), only two patients had undetectable viral load (< 20 copies/mL) and 16 (69.6%) were not under antiretroviral therapy at the time of diagnosis. Treatment-wise, liposomal amphotericin B was used in 18 patients, meglumine antimoniate in four and miltefosine in one. Fourteen (60.9%) were adherent to secondary prophylaxis protocol. A relapse rate of 26.1% was observed (six patients).Discussion: Co-infection is responsible for higher treatment failure rates and more relapses. TCD4+ cell count is the main predictive factor of relapse, and strict adherence to chemoprophylaxis protocols unequivocally results in a reduction of relapse rate. Combined treatment strategies using liposomal amphotericin B and miltefosine yield fewer therapeutic failures than the classic approach.Conclusion: We therefore conclude that alternative, combined therapeutic protocols seem to be a viable solution for these patients.